Leccinum vulpinum Watling: nutritional, antioxidant and antitumour potential - Reis, Filipa S. (2017)
The global economic value of mushrooms is significant, not only due to their value as food [1] but also their medicinal properties, some of them having particularly been described to have antioxidant and antitumour potential [2,3]. Furthermore, some mushroom extracts have reached clinical trials. Additionally, in Japan, PSK (a polysaccharide conjugate isolated from Trametes versicolor (L.) Lloyd), is prescribed as an adjunct to conventional cancer therapies and surgical treatments of colorectal and gastric cancers [4]. The aim of this work was to study the chemical profile of Leccinum vulpinum Watling, regarding its content in nutrients and non-nutrients. Moreover, to study the in vitro antioxidant and antitumour potential of its phenolic extract. L. vulpinum wild samples were collected in Bragança, in the northeastern region of Portugal. The nutritional value was assessed following standard procedures. The individual profiles in soluble sugars, fatty acids and micronutrients were obtained through chromatographic techniques. The antioxidant potential of the phenolic extract was evaluated through the reducing power, DPPH radical-scavenging activity and lipid peroxidation inhibition assays. To assess the antitumour potential, the extract was screened against a panel of human tumour cell lines (MCF-7, NCI-H460, HCT-15 and AGS). Studies of effect on cell proliferation, cell cycle profile and apoptosis were performed on MCF-7 cells. The effect on DNA damage was evaluated with the Comet assay. L. vulpinum showed a nutritional profile with low fat levels, fructose, mannitol and trehalose as the foremost free sugars, and high percentage of mono- and polyunsaturated fatty acids. The main isoforms of vitamin E detected were the β- and γ-tocopherol. L. vulpinum also revealed the presence of phenolic acids (e.g., gallic, protocatechuic and p-hydroxybenzoic acids) and other organic acids (e.g., citric acid). The phenolic extract presented reducing capacity, radical-scavenging activity and lipid peroxidation inhibition. Regarding the antitumour potential, the extract inhibited the growth of all the tested cell lines. In addition, it decreased cellular proliferation, induced apoptosis and caused DNA damage of MCF-7 cells. The present study highlights the importance of conserving the national mycological resources, as a source of bioactive compounds with antioxidant and antitumour activity.